The Role of Green Sukuk in Financing Sustainable Development: A Netnographic Analysis of Investor Sentiment and Discourse - Amir Mukadar; Aan Zulyanto (Socio-Economic and Humanistic Aspects for Township and Industry, 2026)
This study has successfully examined investor sentiment and discourse on green sukuk through a qualitative netnographic approach. Although green sukuk has gained increasing attention as an Islamic sustainable finance instrument, limited research has explored how investors perceive, evaluate, and discuss it in digital environments. This study analyzed 847 text units collected from publicly accessible online platforms, including social media, Islamic finance forums, investment discussion communities, YouTube comment sections, and public blogs. The data were coded inductively using NVivo 14 and analyzed through thematic analysis. The findings identified four dominant themes: investor trust and credibility, financial return expectations, environmental awareness and motivation, and religious motivation. Trust and credibility emerged as the most prominent theme, reflecting investor concerns regarding transparency, certification, issuer reputation, and impact reporting. Financial return expectations showed that investors continue to assess green sukuk through yield, liquidity, risk, and accessibility considerations. Environmental motivation was expressed through concerns about climate action, measurable green impact, and project additionality, while religious motivation reflected Sharia compliance, halal investment identity, and Islamic ethical responsibility. The study demonstrates that investor sentiment toward green sukuk is shaped by the interaction of financial rationality, environmental concern, institutional trust, and religious legitimacy. These findings offer practical implications for issuers, regulators, and Sharia supervisory bodies in strengthening transparency, impact reporting, market credibility, and investor confidence in Islamic sustainable finance.